Indonesian Theater Public in Five Cities on Java Island - J Jaeni (Pascasarjana ISBI Bandung Conference Series, 2025)
The awareness to understand the public of theatrical performance arts has long disappeared from the existence of artists in Indonesia. This side is quite problematic even though it is not a core part of the artist's attention. On the other hand, managers of performing arts buildings, including government agencies related to the development of preservation zones and the development of cultural arts have also never had a movement to map the public performing arts theater as part of the arts ecosystem. At least since the early 2005s, the public theater performance has not been well defined until today in Indonesia. Theatre troupes thrive, theater production rates are high, but the public is shrinking and unidentified. Research methods conducted to map and classify theater performance audiences with a phenomenological approach. This method prioritizes indepth interview work and participant observation targeting the public of theatrical performance arts when watching theater performances in major cities in Indonesia. The results of this study show three public classifications of theatrical performing arts including critical-appreciative, snobis-interactive, and collective-participative. The three groups are always present in the theater performance space. They are part and parcel of a theatrical performance event. Keywords: Theatre; Public Arts; Performance Communication; Art Ecosystem